2010
DOI: 10.1111/j.1439-0264.2009.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Structure of the Adrenal Gland of the Bottlenose Dolphin (Tursiops truncatus) and the Striped Dolphin (Stenella coeruleoalba) from the Adriatic Sea

Abstract: Summary The structure of the adrenal gland was studied in 11 bottlenose dolphins (Tursiops truncatus), and five striped dolphins (Stenella coeruleoalba). These species are legally protected in Croatia. All examined animals died of natural causes and were found stranded along eastern Adriatic coast. In both species the adrenal gland consists of a cortex and a medulla; the cortex is divided into three zones. Whereas in the bottlenose dolphin, there is a zona arcuata which contains columnar cells arranged in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…The zona fasiculata of the African giant rat conforms to those of previous reports being the widest of the three layers of the adrenal cortex comprising about 60-80 % of the cortical tissue (Bacha & Bacha;Junqueira & Carneiro, 2005). The zona fasiculata has the widest radial cells of cuboidal or polyhedral with cords of this zone are separated by sinusoids (Vukovic et al, 2010). A gradual transition from zona fasiculata to zona reticularis with the cells of the zona reticularis having an irregular pattern of anastomosing cords surrounded by sinusoids is similar to previous reports in other mammals (Banks; Vukovic et al).…”
Section: Discussionsupporting
confidence: 76%
“…The zona fasiculata of the African giant rat conforms to those of previous reports being the widest of the three layers of the adrenal cortex comprising about 60-80 % of the cortical tissue (Bacha & Bacha;Junqueira & Carneiro, 2005). The zona fasiculata has the widest radial cells of cuboidal or polyhedral with cords of this zone are separated by sinusoids (Vukovic et al, 2010). A gradual transition from zona fasiculata to zona reticularis with the cells of the zona reticularis having an irregular pattern of anastomosing cords surrounded by sinusoids is similar to previous reports in other mammals (Banks; Vukovic et al).…”
Section: Discussionsupporting
confidence: 76%
“…In guinea pig, reticularis cells penetrated into medulla and also the cortical invagination observed that formed around the blood vessels. So, structures also had been reported in bottlenose dolphin from the Adriatic Sea and it was explained that if organs grow permanently, the invagination can be from overgrowing of tissue during development (Vukovic et al 2009). The cells with granules that are smaller and less electron-dense are epinephrine cells and those with larger and more electron-dense are norepinephrine cells (Steven and Lowe 1991).…”
Section: Discussionmentioning
confidence: 92%
“…The cells of this zone were cuboidal in hamster and polygonal with more vacuoles in guinea pig. The vacuoles caused by numerous empty spaces from dissolution of lipid droplets during processing that described for many domestic animals (Dellmann 1993) and also in humans, but in some animals, for example in the bottlenose dolphin and striped dolphin, was not observed (Vukovic et al 2009). Zona fasciculate in human forms 78/4 % of cortex, in dog and rabbit 60 % of cortex (Tanyolac 1993), and it consists 66/3 % of cortex in porcupine (Yılmazs and Girgin 2005).…”
Section: Discussionmentioning
confidence: 93%
“…By contrast to rabbits, in cattle and some marine mammals, in the medulla, two types of cells located in the layers are distinguished. Epinephrocytes are located on the periphery of the medulla, and the norepinephrocytes in the centre (Clark et al, 2005;Vuković et al, 2010;Barszcz et al, 2016). Also shifts of the medulla towards the periphery of the gland were observed in 42% of ST rabbits.…”
Section: Discussionmentioning
confidence: 97%
“…The mentioned factors also influence the structure of the suprarenal glands of numerous species of rodents (Sheikhian et al, 2014;Olukole et al, 2016;Santos et al, 2016;Finco & Hammer, 2018). Significant species peculiarities were determined in the structure of the suprarenal glands of cetaceans (Vuković et al, 2010) and primates (Tachibana et al, 2015;Raharison et al, 2017). Among the studied animals, surveys frequently detected rabbits in which the structure of the suprarenal glands was studied from the perspective of embryogenesis (Sokolov, 1969;Hussein et al, 2015), blood circulation (Kigata & Shibata, 2018), physiological and pathological conditions (Vinson et al, 1985;Baine et al, 2014) and impact of chemical substances (Chandra, 1975;McCreedy & Harmon, 1992).…”
Section: Introductionmentioning
confidence: 99%